Impact of Plasmatic Progesterone on the Day of Frozen Embryo Transfer in Hormone-induced Cycles - José Metello; Claudia Tomás; Pedro Ferreira; Iris Bravo; MaryJo Branquinho; Samuel Santos-Ribeiro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To establish a relationship between serum progesterone values on the day of frozen blastocyst transfer in hormone-replaced cycles with the probability of pregnancy, miscarriage or delivery. Methods This was an ambispective observational study including all frozen-thawed embryo transfer cycles performed at our department following in vitro fecundation from May 2018 to June 2019. The outcomes evaluated were β human chorionic gonadotropin (β-hCG)-positive pregnancy and delivery. Groups were compared according to the level of serum progesterone on the day of embryo transfer: the 1st quartile of progesterone was compared against the other quartiles and then the 2nd and 3rd quartiles against the 4th quartile. Results A total of 140 transfers were included in the analysis: 87 with β-HCG>10 IU/L (62%), of which 50 (36%) delivered and 37 had a miscarriage (42%).Women with lower progesterone levels (< 10.7ng/mL) had a trend toward higher β-HCG-positive (72 versus 59%; p>0.05), lower delivery (26 versus 39%; p>0.05) and higher miscarriage rates (64 versus 33%; p<0.01). Comparing the middle quartiles (P25-50) with those above percentiles 75, the rate of pregnancy was similar (60 versus 57%; p>0.05), although there was a trend toward a higher number of deliveries (43 versus 31%; p>0.05) and a lower number of miscarriages (28 versus 45%; p>0.05). These differences were not statistically significant. Conclusion There were no differences in pregnancy and delivery rates related with the progesterone level when measured in the transfer day. The miscarriage rate was higher in the 1st quartile group.